Association between interpregnancy interval and hypertensive disorders of pregnancy: Effect modification by maternal age. Issue 4 (15th June 2021) - Gebremedhin, Amanuel T.; Tessema, Gizachew A.; Regan, Annette K.; Pereira, Gavin
Abstract: Background: Short and long interpregnancy intervals (IPI) are associated with increased risk of hypertensive disorders of pregnancy, yet whether this association is modified by maternal age remains unclear. Objectives: To examine if the association between IPI and hypertensive disorders of pregnancy varies by maternal age at birth prior to IPI. Methods: We conducted a population‐based cohort study of all mothers who had their first two (n = 169 896) consecutive births in Western Australia (WA) between 1980 and 2015. We estimated the risk of preeclampsia and gestational hypertension for 6 to 60 months of IPI according to maternal age at birth prior to IPI (<20 years, 20‐24, 25‐29, 30‐34 and ≥35 years). We modelled IPI using restricted cubic splines and reported adjusted relative risk (RRs) with 95% CI at 6, 12, 24, 36, 48 and 60 months, with 18 months as reference. Results: The risk of preeclampsia was increased at longer IPIs (60 months) compared to 18 months for mothers 35 years or older (RR 2.19, 95% confidence interval (CI) 1.14, 4.18) and to a lesser extent for mothers 30‐ to 34 years old (RR 1.43, 95% CI 1.10, 1.84). Compared to 18 months, the risk of preeclampsia was lower at 12 months of IPI for mothers younger than 20 years (RR 0.74, 95% CI 0.57, 0.96), but not for mothers 35 years or older (RR 0.62, 95% CI 0.36, 1.07). There was insufficient evidence for increased risk of hypertensive disorders of pregnancy at shorter IPIs of <18 months for mothers of all ages. Conclusions: Our findings challenge the "one size fits all" recommendation for an optimal IPI, and a more tailored approach to family planning counselling may be required to improve health.